Role of National Land Board Office in Implementation of Prohibition of Absentee Land Ownership - Ajeng Savira Pravitasari (Sultan Agung Notary Law Review, 2021)
The research objectives are: 1) To find out and analyze the factors that cause absentee land ownership in Kendal Regency. 2) Knowing about the role of the Kendal Regency Land Agency in dealing with and solving land problemsabsentee. The data used in this study are primary data, secondary data, and tertiary data that can support the assessment, which is then analyzed using empirical juridical methods. Based on the results of data analysis, it is concluded that: 1) in Article 3 paragraph (1) of Government Regulation Number 224 of 1961 jo. Government Regulation Number 41 of 1964 (State Gazette of the Republic of Indonesia of 1961 Number 280, Supplement to the State Gazette Number 2322 hereinafter referred to as PP Number 224 of 1961, states that: Agricultural land owners who reside outside the sub-district where the land is located, within a period of 6 (six) months are required to transfer their land rights to another person in the sub-district where the land is located or move to the sub-district where the land is located. The main factors that cause absentee land ownership are from the community that the community lacks legal awareness, and only wants to seek economic benefits derived from absentee land ownership. Cultural factors such as inheritance and infrastructure. In the facilities and infrastructure there are no reports that are helpful in overcoming absentee land ownership from Village and District officials, as well as a lack of coordination and cooperation. 2) in overcoming absentee land problems, the National Land Agency has a role and contribution to reduce absentee land ownership in Kendal Regency, namely by carrying out legal enforcement by conducting legal counseling that is directed and carried out continuously widely to the community. This counseling can be done by coming to the field to collect or monitor the state of the inventory to the regions, namely monitoring the sub-districts, where the sub-district is a center rather than a transfer of rights so that there is no absentee land sale and purchase.